Pengaruh Current Ratio, Return On Assets Dan Debt To Equity Ratio Terhadap Nilai Perusahaan Pada PT Indah Kiat Pulpen Dan Paper TBK - Vivi Mutlak; M.Rimawan; Ovriyadin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of Current Ratio (CR), Return on Assets (ROA), and Debt to Equity Ratio (DER) on the firm value of PT Indah Kiat Pulp and Paper Tbk. Firm value is a crucial indicator for investors in assessing a company’s performance and future prospects. The research uses a quantitative approach with descriptive and verification methods. The data used are secondary data obtained from the company's annual financial reports for the period 2018 to 2023. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results show that partially, ROA has a positive and significant effect on firm value, indicating that higher profitability leads to higher firm value. DER has a negative and significant effect, meaning that a capital structure with a high proportion of debt tends to reduce firm value. Meanwhile, CR does not have a significant effect on firm value, indicating that liquidity level does not necessarily influence investor assessments. Simultaneously, the three independent variables significantly influence firm value. These findings suggest that management should focus more on asset efficiency and capital structure management to enhance company value.